An investigation into the effect of particulate solids on certain antimicrobial preservatives in pharmaceutical and cosmetic suspensions - Horn, Norman Robert (Rhodes University, Faculty of Pharmacy, Pharmacy, 1978)
Pharmaceutical and cosmetic preparations must be formulated so as to assure elegance of appearance, efficacy of ingredients and a satisfactory shelf life as the product. If the formulation is not self-preserving and if it contains material which could act as a substrate for growth of micro-organisms, the shelf life aspect involves, in addition to several other factors, the choice of a suitable antimicrobial preservative. Such preservatives, when present in the minimum effective concentration, are unfortunately prone to interact with many other materials. A number of papers on the inactivation of preservatives by containers, filters and formulation components have been published. The field has been adequately reviewed by de Navarre (1962), Wedderburn (1964) and, more recently, by Coates (1973). From these reviews and from a study of the literature it became apparent that relatively little work had been done on interactions between preservatives and solid particles in aqueous suspension. Consequently, a range of preservatives not previously investigated in this respect was tested for loss of activity in the presence of fifteen powders commonly used in aqueous suspension in pharmaceutical and cosmetic formulations. In view of the information obtained in this preliminary study and after the development of more satisfactory analytical techniques it was decided to study in greater depth the interaction between these powders and selected organomercurials and quaternary ammonium compounds.
Keywords: Drugs -- Preservation; Drugs -- Microbiology; Cosmetics -- Preservation; Cosmetics -- Microbiology